QUALIPAED—A retrospective quality control study evaluating pediatric long axial field-of-view low-dose FDG-PET/CT - Honoré d’Este, Sabrina; Andersen, Flemming Littrup; Schulze, Christina; Saxtoft, Eunice; Fischer, Barbara Malene; Andersen, Kim Francis (Frontiers in Nuclear Medicine, 2024)
Pediatric patients have an increased risk of radiation-induced malignancies due to their ongoing development and long remaining life span. Thus, optimization of PET protocols is an important task in pediatric nuclear medicine. Long axial field-of-view (LAFOV) PET/CT has shown a significant increase in sensitivity, which provides an ideal opportunity for reduction of injected tracer activity in the pediatric population. In this study we aim to evaluate the clinical performance of a 2-[ 18 F]FDGtracer reduction from 3MBq/kg to 1.5MBq/kg on the Biograph Vision Quadra LAFOV PET/CT. The first 50 pediatric patients referred for clinical whole-body PET/CT with 1.5MBq/kg 2-[ 18 F]FDG, were included. A standard pediatric protocol was applied. Five reconstructions were created with various time, filter and iteration settings. Image noise was computed as coefficient-of-variance (COV=SD/mean standardized-uptake-value) calculated from a spherical 20-50mm (diameter) liver volume-of-interest. Sets of reconstructions were reviewed by one nuclear medicine physicians, who reported image lesions on a pre-defined list of sites. Paired comparison analysis was performed with significance at PB<0.05 (Bonferroni corrected).All reconstructions, except one, achieved a COVmean (0.08-0.15) equal to or lower than current clinical acceptable values (COVref≤0.15). Image noise significantly improved with increasing acquisition time, lowering iterations (i) from 6i to 4i (both with five subsets) and when applying a 2mm Gauss filter (PB<0.001). Significant difference in lesion detection was seen from 150s to 300s and from 150s to 600s (PB=0.006-0.007). 99% of all lesions rated as malignant could be found on the 150s reconstruction, while 100% was found on the 300s, when compared to the 600s reconstruction.Injected activity and scan time can be reduced to 1.5MBq/kg 2-[ 18 F]FDG with 5min acquisition time on LAFOV PET/CT, while maintaining clinical performance in the pediatric population. These results can help limit radiation exposure to patients and personnel as well as shorten total scan time, which can help increase patient comfort, lessen the need for sedation and provide individually tailored scans.